Link technology to your long-terms business goals : how to use technology to mobilize your people, strategy and operations - Praz (Apress, 2022)
Link the use of technology with long-term business goals to optimize the core elements in your organization: people, strategy, and operations. This book will show you how effective planning of processes and execution of strategies with the help of technology can bring about an organization-wide increase in productivity and performance. Business environments have grown increasingly competitive. Before an organization realizes what has happened, it can lose or gain market share. Being agile is the key to success. This book covers the processes that can help your enterprise be agile and follow best practices when executing your business strategy. You'll review case studies from real-world experiences that dive deep into the problems a business encounters and the ways to solve those challenges. They deal with the different ways in which your organization can achieve dramatic performance improvements by changing your companys processes. The book also explains how objectives and key results can be used to align business teams for increased productivity. With Use Tech to Mobilize Your People, Strategy, and Operations you'll learn how the intensity of core processes can ensure that growth does not wane in your organization. .